Eficiência da ação fotodinâmica em Mycobacterium massiliense - Arantes, Danilo Pastori (Universidade Federal de São Carlos, 2012)
In Brazil there was an increase of post-surgical infections by rapidly growing mycobacteria, mainly Mycobacterium massiliense, leading the Agency for Sanitary Surveillance (ANVISA) to establish standards for the mandatory notification of cases occurring nationwide. In order to deal with a major public health problem, this study aimed to determine the efficiency of using antimicrobial photodynamic inactivation (PDIa) in Mycobacterium massiliense for future use in the treatment of agent infections. The objective was to test in vitro technique the PDI to control Mycobacterium massiliense to determine the best light dose and concentration of each photosensitizer (FS). To accomplish this search were used two FS: Photogem® and salt Curcumin (N-Methyl-D-Glucominato of Curcumin, 31.8%). As a light source for radiating a BioTable ® operated at 630nm (red light) for Photogem ® and 460nm (blue light) to the salt of curcumin. After the standardized inoculum was added to the sample analyzed in triplicate to a 24 well plate which contained 500μl aliquots of the inoculum +500 μ l of the FS for the study groups tested, and the control group containing 1 ml of inoculum, and five minutes as time incubation (protected from light). After expiration of the irradiation time in accordance with the previously analyzed fluences of the tested groups and subsequent dilution of the sample to the value of 10-5, 100mL sample were plated in triplicate on 7H10 agar + OADC 10% and maintained at 37 for about 5 days with subsequent counting of colony forming units. Based on the results, they showed that FS Photogem ® until the concentration of 1000 μg/Ml was not effective in reducing the number of CFU of M. massiliense. In contrast, the FS Salt Curcumin was effective at concentrations of 1300 μg/Ml with a light dose 50 J/cm2 compared to controls. Thus, these data suggest that the salt FS Curcumin in photodynamic action is a viable alternative for reducing M massiliense when tested in vitro.
Efficiency of Photodynamic Action on Mycobacterium massiliense
Keywords: Terapia fotodinâmica; Micobactérias; Mycobacterium massiliense; Curcumina; PDT; TDF; Photogem®; Mycobacterium; Curcumin; OUTROS